2009
DOI: 10.1002/app.30175
|View full text |Cite
|
Sign up to set email alerts
|

The use of compatible blend of styrene‐vinylacetate copolymer/natural rubber latex in pressure‐sensitive adhesive applications by using irradiation and chemical initiation

Abstract: Thermoplastic elastomers from blends of styrene‐vinylacetate copolymer latex (S‐VAc) and natural rubber latex (NRL) as a hydrophilic/hydrophobic blend have been prepared by the solution‐casting technique. Compatibility between S‐VAc and NRL was confirmed at all ratios of the blend mixing through the measurements of water absorption, thermogravimetric analysis, and scanning electron microscope. The prepared blend was studied for pressure‐sensitive adhesive (PSA) application. Nonylphenol ethoxylate (NPE) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They concluded that the selfadhesion energy of the blend increases with contact time. The pressure-sensitive adhesive applications of compatible blend of styrene-vinyl acetate copolymer/natural rubber latex by irradiation and chemical initiation were also reported by Magida et al [8]. On the other hand, Stephen et al [9] published the adhesive formulations with ternary blends using simplex lattice design whereas Da Silva et al [10] and Riyajan and Pheweaw [11] investigated the adhesive performance of synthetic rubber blend and natural rubber blend, respectively.…”
Section: Introductionmentioning
confidence: 70%
“…They concluded that the selfadhesion energy of the blend increases with contact time. The pressure-sensitive adhesive applications of compatible blend of styrene-vinyl acetate copolymer/natural rubber latex by irradiation and chemical initiation were also reported by Magida et al [8]. On the other hand, Stephen et al [9] published the adhesive formulations with ternary blends using simplex lattice design whereas Da Silva et al [10] and Riyajan and Pheweaw [11] investigated the adhesive performance of synthetic rubber blend and natural rubber blend, respectively.…”
Section: Introductionmentioning
confidence: 70%
“…It was found that the self-adhesion energies of the rubber blend increase with contact time with the glass substrate. Magida et al [4] investigated the pressure-sensitive adhesive applications of compatible blend of styrene-vinyl acetate copolymer/natural rubber latex by using irradiation and chemical initiation. Meanwhile, Da Silva et al [5] found that a single resin improves the adhesion property of styrene-isoprene-styrene (SIS)/styrenebutadiene-styrene (SBS) hot melt pressure-sensitive adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the effect of testing rate on adhesion properties of acrylonitrile–butadiene rubber (NBR)/SMR L blend-based PSA was investigated by Poh and Lamaming. 5 On the other hand, Magida et al 6 have studied the use of compatible blend of styrene–vinylacetate copolymer/natural rubber latex in PSA applications using irradiation and chemical initiation. In view of the absence of data report in this field of interest, we have carried out a systematic study to understand the effect of blend ratio and testing rate on the adhesion property of ENR 25/NBR-based adhesives.…”
Section: Introductionmentioning
confidence: 99%